The Black book - Harris, M. A., 1908-1977; Levitt, Morris, 1938-; Furman, Roger, 1924-1983.; Smith, Ernest; Morrison, Toni; Cosby, Bill, 1937-; Ribik, Jack (New York : Random House, 1974)
Copiously illustrated scrap-book on folk culture of Black people from early days of slavery through the present. Includes photographs, illustrations, advertisements, plans, form documents, sheet music, and more all printed in facsimile.
With an introduction by Bill Cosby.
Book and jacket design by Jack Ribik.
Toni Morrison, a senior editor at Random House at the time of the book's publication, is the uncredited compiler of this book, which includes an uncredited poem by her on the jacket flaps. The 35th anniversary edition (2009) prints the poem as a preface and credits Morrison as the author. Her mother appears on the jacket cover.--See "Ghosts in the House: How Toni Morrison fostered a generation of black writers" in the October 27, 2003 issue of the New Yorker.
NLJCols20082021
Keywords: African Americans -- History -- Miscellanea; African Americans; Noirs -- Etats Unis -- Histoire; Blacks -- History -- Miscellanea; History; Trivia and miscellanea; Trivia and miscellanea